INTERTEXTUAL HARMONY OF SURAH AL-BAQARAH IN THE VERSES OF THE QURAN AND THE TEXTS OF HADITH (Eureka Journal of Language, Culture & Social Change, 2026)
Intertextual analysis of Surah Al-Baqarah with hadiths is, in fact, a combination of two different perspectives: the first perspective is the continuity of the Quran-Sunnah in the Islamic scientific tradition (explanation, taqiyid, takhsis, application), the second perspective is the intertextual relationship in modern textual studies (referentiality, citation, allusion, paraphrase, resemantization). These two perspectives do not deny each other; on the contrary, one shows “status and evidence”, the other “mechanism and functioning of meaning”. Surah Al-Baqarah is very convenient for demonstrating this harmony, because it is a kind of “social laboratory” within the Quran: there is also the psychology of faith, there is also the rhythm of worship, there is also the mechanics of legal transactions, there is also the educational conclusion of historical stories, there is also the subtle tone of prayer and submission.
Keywords: Quran, Hadith, Dua, Meaning, Dhikr, Style, Faith, Kufr, Verse.